Translating as a way of writing history: Father du Creux's Historiæ Canadensis and the Relations jésuites of New France. Issue 1 (February 2015) - Hamel, Amélie
<x xml:space="preserve">Abstract</x> The Historiæ Canadensis, seu Nouæ‐Franciæ libri decem, ad annum vusque Christi MDCLVI is a translation commissioned by the Society of Jesus in France in order to disseminate information concerning its evangelical activities in New France in the first decades of the seventeenth century. The source text is a series of reports written by the Jesuit missionaries in simple, unadorned French prose and printed hastily and cheaply. The form is that of a travel narrative and the tone is often grim. In 1664, Father François du Creux, a Jesuit, rewrote some of these texts, producing what might be called a three‐dimensional 'translation' effecting their form, language, and material features. This article explores the ways in which he restructured and reorganized the individual missionary adventures into a historical, narrative framework and turned the French text into Latin, enriching it and elevating the tone as he did so. It also discusses the manner in which expensive engravings illustrating the narratives synthesized them by providing a context and an edifying dimension. Our study demonstrates how these features transform the Relations by combining to give the translation a certain 'gravitas', thus widening its appeal and extending its message to a new, larger, and more varied readership.